SOME PROBLEMS BETWEEN THE NATIVE LANGUAGE OF FOREIGN STUDENTS AND LEARNING ENGLISH - Radjapova Nargiza Bekmuradovna (American Journals, 2022)
This article is devoted to considering the peculiarities of using the native language in the process of teaching a foreign language. The process of language education in a foreign language is closely related to the question of the interaction of two language systems in the speaker's mind. All mental processes of students, their mental activities are closely related to their native language, phonetics, grammar and lexical structure.
Keywords: foreign languages, native students, teaching process, speaking.